2020
DOI: 10.1371/journal.pone.0229366
|View full text |Cite
|
Sign up to set email alerts
|

Improved iterative reconstruction method for Compton imaging using median filter

Abstract: A Compton camera is a device for imaging a radio-source distribution without using a mechanical collimator. Ordered-subset expectation-maximization (OS-EM) is widely used to reconstruct Compton images. However, the OS-EM algorithm tends to over-concentrate and amplify noise in the reconstructed image. It is, thus, necessary to optimize the number of iterations to develop high-quality images, but this has not yet been achieved. In this paper, we apply a median filter to an OS-EM algorithm and introduce a median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…Sakai et al reported that %CV increased as the number of iterations was increased using ordered-subset expectation maximization. The method statistically estimates the source distribution, thus emphasizing the statistical noise in the image (18). Contrast is one of the most important parameters to evaluate because detection of hot spots is used for diagnosis in bone SPECT (19).…”
Section: Discussionmentioning
confidence: 99%
“…Sakai et al reported that %CV increased as the number of iterations was increased using ordered-subset expectation maximization. The method statistically estimates the source distribution, thus emphasizing the statistical noise in the image (18). Contrast is one of the most important parameters to evaluate because detection of hot spots is used for diagnosis in bone SPECT (19).…”
Section: Discussionmentioning
confidence: 99%
“…OSEM works in the same manner as MLEM, but it uses data divided into subsets (portions of measured data), and updates are performed for each subset. If subsets are created appropriately, image convergence can be greatly accelerated with little degradation in the image quality [ 81 , 207 , 208 ].…”
Section: Image Reconstruction Methods For Compton Imagingmentioning
confidence: 99%
“…However, the convergence speed of the adopted iterative reconstruction method was not sufficiently high because the imaging algorithms considered the high-energy γ-ray source located at a far distance, and the simulation programs developed at that time considered the simple detector system. Some studies have recently been conducted to improve the MLEM and compare it with other imaging models, with a focus on the application of Compton cameras in nuclear medicine and particle therapy [ 81 , 210 , 211 , 212 , 213 ]. Yabu et al [ 214 ] reported the superiority of the LM-MLEM method over SBP using a Si/CdTe Compton camera.…”
Section: Image Reconstruction Methods For Compton Imagingmentioning
confidence: 99%
See 2 more Smart Citations